Probiotics supplements for the prevention of atopic dermatitis in children: an umbrella review - Zhong, Ling; Su, Jia; Zhou, Xiyuan; Wan, Huiying (Frontiers in Nutrition, 2025)
IntroductionPrevious meta-analyses of multiple studies have suggested that probiotics supplementation plays a role in reducing the risk of atopic dermatitis (AD). However, the conclusions of these studies remain controversial.MethodsWe conducted an umbrella review of meta-analyses to comprehensively analyze and evaluate the evidence regarding the association between probiotics and AD. We searched PubMed, Web of Science, Embase, Spous, and Cochrane Library databases for meta-analyses and systematic reviews up to October 2024. Our selection criteria encompassed meta-analyses of cohort studies, case–control studies, and randomized controlled clinical trials investigating the associations between probiotics and the risk of AD. We also assessed the levels of evidence for these associations using the AMSTAR 2 criteria.ResultsA total of 32 eligible articles, including 126 meta-analyses, were included for qualitative synthesis in this umbrella review. The results indicate that probiotics supplementation is associated with a reduced risk of AD. The subgroup analysis indicates that supplementation with Lactobacillus spp., single-strain, and multi-strain probiotics is associated with a reduced risk of AD, with multi-strain formulations potentially demonstrating more pronounced effects. Furthermore, both combined prenatal and postnatal supplementation, as well as postnatal supplementation alone, contribute to a reduction in AD risk.DiscussionProbiotics supplementation may help reduce the risk of AD, with early-life administration playing a key role. Future research should focus on well-designed randomized controlled trials that account for potential sources of bias in order to provide evidence-based public health recommendations.Systematic review registrationPROSPERO (International00 Prospective Register of Systematic Reviews) under the registration number CRD42024599789. The publicly accessible registration record is available at: https://www.crd.york.ac.uk/PROSPERO/view/CRD42024599789.